Myths and Legends, An Intertextual Application in Games and Toys - Maryam Jalali; Azam Hakim (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Nowadays, new topics have appeared in interdisciplinary approaches to research. Such topics are not limited to theoretical aspects of the research. In humanities, they have been helpful in practical applications of literature. For example, involvement of literature in games and toys has been a breakthrough in the audience's reception of literature. Semiologists such as Roland Barthes have studied games and toys as texts along with many other sign systems. Having roots in the culture and literature (including myths and legends) of every land, these texts have the potential for re-production and reception in another artistic form, and thereby, provide the condition for practical application of literature. In this paper, after discussing the textuality of games and toys, we have addressed questions regarding elements of intertextuality in them derived from myths and legends and the implications of this interdisciplinary approach and its practical application on literature. This qualitative, descriptive- analytical paper, which considers games and toys as signs and texts, offers the readers a different way of reading of myths and legends. The discovery of the intertextual relationships between games, toys and myths and legends of any land is considered a strategy for creating games with a literary context and might also create a specific genre.